Understanding the health impacts of the climate crisis - Mark Maslin; Raina D. Ramnath; Gavin I. Welsh; Sanjay M. Sisodiya (Future Healthcare Journal)
The climate crisis is the greatest threat to global health. Anthropogenic greenhouse gas emissions have increased the temperature of the Earth by over 1.5 °C and caused sea levels to rise by over 24 cm since the beginning of the 20th century. 2024 was the warmest year on record and the last 10 hottest years have all occurred in the last 10 years. Climate models suggest that global surface temperature could rise between 1.5 °C and 5.5 °C compared with the pre-industrial period by 2100, and sea-level rise could be between 0.5 m and 1.3 m. Climate change is already causing significant shifts in weather patterns and an increase in extreme weather events around the world, including droughts, heatwaves, wildfires, storms and floods. These are having an impact on the spread of infectious diseases and the severity of non-infectious diseases. Climate change is already causing food and water insecurity, increasing levels of malnourishment and the burden of disease. The unpredictable impacts of climate change and the perceived inaction from local, national and international leaders, is creating anxiety that is contributing to deteriorating mental health, particularly in young people. The health impacts of climate change will increase in the future if nothing is done to curb greenhouse gas emission. We need action to deal with the climate crisis while improving the health, security and income of the very poorest people in our global society. We must plan for a net zero world that provides healthy, safe and low environmental impact lives for 10 billion people by 2050.